A Neutral Tetraphosphacyclobutadiene Ligand in Cobalt(I) Complexes1. (4th December 2014) - Yao, Shenglai; Lindenmaier, Nils; Xiong, Yun; Inoue, Shigeyoshi; Szilvási, Tibor; Adelhardt, Mario; Sutter, Jörg; Meyer, Karsten; Driess, Matthias
Abstract The unusual reactivity of the newly synthesized β‐diketiminato cobalt(I) complexes, [(LDepCo)2] (2 a, LDep=CH[C(Me)N(2, 6‐Et2C6H3)]2) and [LDippCo⋅toluene] (2 b, LDipp=CH[CHN(2, 6‐iPr2C6H3)]2), toward white phosphorus was investigated, affording the first cobalt(I) complexes [(LDepCo)2(μ2:η4, η4‐P4)] (3 a) and [(LDippCo)2(μ2:η4, η4‐P4)] (3 b) bearing the neutral cyclo‐P4 ligand with a rectangular‐planar structure. The redox chemistry of 3 a and 3 b was studied by cyclic voltammetry and their chemical reduction with one molar equivalent of potassium graphite led to the isolation of [(LDepCo)2(μ2:η4, η4‐P4)][K(dme)4] (4 a) and [(LDippCo)2(μ2:η4, η4‐P4)][K(dme)4] (4 b). Unexpectedly, the monoanionic Co2P4 core in 4 a and 4 b, respectively, contains the two‐electron‐reduced cyclo‐P42− ligand with a square‐planar structure and mixed‐valent cobalt(I, II) sites. The electronic structures of 3 a, 3 b, 4 a, and 4 b were elucidated by NMR and EPR spectroscopy as well as magnetic measurements and are in agreement with results of broken‐symmetry DFT calculations.